Potential of quixaba (Sideroxylon obtusifolium) latex as a milk-clotting agent - Silva,Anna Carolina da (2013)
There are several obstacles to the use of chymosin in cheese production. Consequently, plant proteases have been studied as possible rennet substitutes, but most of these enzymes are unsuitable for the manufacture of cheese. The aim of this study was to evaluate the potential of latex from Sideroxylon obtusifolium as a source of milk-clotting proteases and to partially characterize the enzyme. The enzyme extract showed high protease and coagulant activities, with an optimal pH of 8.0 and temperature of 55 °C. The enzyme was stable in wide ranges of temperature and pH. Its activity was not affected by any metal ions tested; but was inhibited by phenylmethanesulfonyl fluoride and pepstatin. For the coagulant activity, the optimal concentration of CaCl2 was 10 µmol L- 1. Polyacrylamide gel electrophoresis showed four bands, with molecular weights between 17 and 64 kDa. These results indicate that the enzyme can be applied to the cheese industry.